Desa Tangguh Bencana di Desa Widarapayung Wetan, Kecamatan Binangun, Kabupaten Cilacap (Pengembangan Desa Tangguh Bencana Berbasis Masyarakat Desa) - Vinandya Asti Aprilinda; Rahmad Purwanto W; Christine Diah Wahyuningsih (Universitas 17 Agustus 1945 Semarang, 2023)
Research on Community-Based Disaster Risk Reduction in Widarapayung Wetan Village is motivated by the geographical location of Widarapayung Wetan Village which is directly adjacent to the Indian Ocean in the south which contains the Indo-Australian plate. . The method used in this research is qualitative with descriptive method. Data collection techniques used are in-depth interviews and documentation studies. Aspects examined in this study are efforts to identify threats, efforts to reduce vulnerabilities and efforts to increase capacity. The results of the study indicate that disaster risk reduction efforts have been carried out by the people of Widarapayung Wetan Village. However, the efforts made have not been maximized due to several factors, especially the lack of active disaster organizations in the village of Widarapayung Wetan, namely the Community-Based Disaster Preparedness (CBAT) in disaster risk reduction efforts. Aspects of threat recognition carried out by the Widarapayung Wetan village community include socialization, disaster risk analysis. Aspects of reducing vulnerability are carried out through planting hard trunked trees, installing sirens, installing evacuation signs, and mapping. Aspects of capacity building, namely through socialization, simulations, disaster training, the establishment of the FPRB, the establishment of a Disaster Resilient Village, and the existence of institutions at the village level.